2017
DOI: 10.1155/2017/9282565
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits as Predictor of Emotional Intelligence among the University Teachers as Advisors

Abstract: The focus of the present study was to investigate personality traits as the predictor of emotional intelligence (EI) among the university teachers working as student advisors. A sample of the study comprised 100 student advisors (male = 50; female = 50). The age range of the sample was 21–40 years. Schutte Emotional Intelligence Scale (SEIS) and Big Five Inventory (BFI) were used to measure emotional intelligence (EI) and personality traits. For the statistical analysis of the data, T-test and regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 16 publications
5
24
0
Order By: Relevance
“…They found that extroversion, agreeableness, and openness to experience emerged as significant predictors of EI. The study also concluded that conscientiousness and neuroticism have no impact on EI [13].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They found that extroversion, agreeableness, and openness to experience emerged as significant predictors of EI. The study also concluded that conscientiousness and neuroticism have no impact on EI [13].…”
Section: Introductionmentioning
confidence: 91%
“…An important predictor of EI is personality [13] defined as individual differences in characteristic patterns of thinking, feeling and behaving [14]. An important property of personality traits is being stable across time [15] and situations [16], which makes it characteristic of each individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, the research study conducted by Alghamdi, Aslam & Khan (2017), involving 100 university teachers in Saudi Arabia, revealed no differences in Emotional Intelligence between genders, a discovery also supported by the study "Relationship between Job Satisfaction and Emotional Intelligence among school teachers of Kangra District of Himachal Pradesh", conducted by Shinu, Renu and Lalita (2016).…”
Section: Discussionmentioning
confidence: 61%
“…EI is the ability to manage emotions and interact effectively with others [2]. EI is the capability to have a precise insight of appraising, to articulate one's own, and others' emotions and to retrieve and create feelings as soon as they facilitate thinking [3], [4]. People with high EIs are sensitive to the moods and temperaments of others, display empathy, appreciate multiple perspectives when approaching situations [2], and employ emotions in problem resolution [4].…”
mentioning
confidence: 99%